PERCEPCIÓN DE LOS BENEFICIOS DE LA TENENCIA DE ANIMALES DE COMPAÑÍA EN TRES GRUPOS POBLACIONALES DE LA HABANA, CUBA - Hugues H, Beatriz (2014)
The study aimed to determine the perception of three groups of people in Havana, Cuba [breeders of ornamental birds (CAO), veterinary medicine students (E), and pet owners (RAC)] through a survey on pet ownership in relation to personal satisfaction and health. Results showed that 99% of the persons were satisfied of sharing their lives with companion animals. They also pointed out high mental health benefits (84, 73, and 80% for CAO, E, and RAC respectively). In relation to metabolic control, 58 and 96% of the persons suffering any of these diseases indicated that were motivated to take better care. The results showed that the surveyed persons in the three population groups perceive that pet ownership brings them physical and mental health benefits.